A 25-Residue Peptide From Botrytis cinerea Xylanase BcXyn11A Elicits Plant Defenses - Frías, Marcos; González, Mario; González, Celedonio; Brito, Nélida (Frontiers in Plant Science, 2019)
Plants activate defense responses against a possible pathogen once pattern-recognition receptors (PRRs) perceive the presence of pathogen-associated molecular patterns (PAMPs). Glycosyl hydrolase family 11 (GH11) endoxylanases from Trichoderma, Fusarium and Botrytis species have been described as being able to induce the defense response in plants, in a way that is independent of its enzymatic activity. However, until now, it has not been possible to establish with certainty which regions of these enzymes are recognized by plants as PAMPs. We show here for the first time that a short 25-residue peptide (named Xyn25) from the Botrytis cinerea xylanase BcXyn11A can reproduce by itself all the effects observed for the treatment of plants with the whole BcXyn11A protein. These include necrosis on leaves, seedling growth inhibition, induction of a ROS burst, electrolyte leakage, cytoplasm shrinkage, autofluorescence, cell death, and induction of defense genes. Two highly-conserved 4-amino acid regions within Xyn25 were shown to be necessary for the elicitation activity by substituting them with tracts of four alanine residues.